Climate change, media & culture : critical issues in global environmental communication - Pinto, Juliet; Gutsche Jr., Robert E.; Prado, Paola (Emerald Publishing Limited, 2019)
The acceleration of massive global climate change creates a nexus for the examination of power, political rhetoric, science communication, and sustainable development. This book provides an international view of twenty first century environmental communication, from journalism to artistic expression, to critically explore mediated expressions of climate change. Seeking to understand how government policies, environmental news reports, corporate messages, and social influences communicate the complexities of climate change to the public, this book examines the roles that journalism, entertainment, and strategic messaging play in mediating meanings of science, health, economy, and sustainable solutions. It considers the critical importance of the study of climate change communication, which is inherently interdisciplinary, as well as globally and locally impactful. With topics ranging from communicating resilience through environmental journalism and linguistics, the storytelling of climate change explanations in the news, the role of visual communication in capturing and addressing climate change, and the communication of the health impacts of climate change, this book will appeal to undergraduate and graduate students and scholars in environmental sciences, international relations and politics, media, journalism and mass communication.